A National Survey of Social Workers Focusing on Attitudes, Knowledge, and Practice Behaviors for Educating Patients About Advance Directives: Implication During COVID19. (June 2022) - Nedjat-Haiem, Frances R.; Cadet, Tamara J.; Parada, Humberto; Mishra, Shiraz I.; Bullock, Karen
Social workers have a critical role on medical teams for facilitating effective conversations about advance care planning (ACP) in palliative and end-of-life care. Engaging patients in such conversations may be influenced by clinicians' attitudes. During the COVID19 pandemic, the need to examine barriers to serious illness care across healthcare settings and areas of specialty practice became abundantly clear. This study examines: (1) social workers' attitudes about ACP and (2) factors that influence the completion of advance directives (ADs). Using a cross-sectional study design, we surveyed 142 social workers on their knowledge, attitudes, and behaviors related to ADs. Using exploratory factor analyses, we identified 2 provider practice attitudes factors, 3 perceived barriers factors, and 2 perceived importance of AD factors. We then used logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for each of the factors in association with the frequency social workers reported educating patients about ADs. While various positive and negative attitudes and barriers toward educating patients are important factors to consider, social workers' perceptions of the importance of engaging patients in ACP education was the most important factor that influenced their behaviors. The odds of always/often (vs. sometimes/rarely/never) educating patients about ADs in their practice were greater for those social workers who reported they see the importance of AD decision-making (OR = 3.21, 95%CI = 1.83-5.62) and confirming goals-of-care (OR = 1.76, 95%CI = 1.03-3.01). Social worker's ACP knowledge and skills for educating patients are important in initiating conversations prior to a health crisis, especially important for developing a comprehensive care plan.